2020
DOI: 10.5091/plecevo.2020.1661
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Tricalysia elmar sp. nov. (Rubiaceae, Coffeeae), and cloud forest of the Cameroon Highlands

Abstract: Background and aims – This paper reports a further discovery in the context of a long-term botanical survey in the Cross River-Sanaga interval of west-central Africa, focussing on species discovery and conservation.Methods – Normal practices of herbarium taxonomy have been applied to study the material collected. The relevant collections are stored in the Herbarium of the Royal Botanic Gardens, Kew, London and at the Institute of Research in Agronomic Development – National Herbarium of Cameroon. Key results –… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Most of these new species were first described as point or near-endemics, but several have, with more research, been found to be more widespread e.g. Tricalysia elmar Cheek (Rubiaceae, Cheek et al . 2020a) now known to extend from Mt Kupe and Bali-Ngemba to e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these new species were first described as point or near-endemics, but several have, with more research, been found to be more widespread e.g. Tricalysia elmar Cheek (Rubiaceae, Cheek et al . 2020a) now known to extend from Mt Kupe and Bali-Ngemba to e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Korupodendron songweanum Litt & Cheek (Vochysiaceae, Litt & Cheek 2002), Vepris montisbambutensis Onana (Onana et al 2015), Vepris mbamensis Onana (Onana et al 2019), Vepris zapfackii Cheek & Onana (Cheek & Onana 2021) and Carapa oreophila Kenfack (Meliaceae, Kenfack 2011).Most of these new species were first described as point or near-endemics, but several have, with more research, been found to be more widespread e.g. Tricalysia elmar Cheek (Rubiaceae,Cheek et al 2020a) now known to extend from Mt Kupe and Bali-Ngemba to e.g. the Rumpi Hills(Lachenaud pers.…”
mentioning
confidence: 99%
“…aff. ferorum is now published as T. elmar Cheek and is known also from Mt Kupe, Ngovayang and the Rumpi Hills (Cheek et al 2020b;Lachenaud pers. comm.…”
Section: The Endemic Plants Of Bali Ngembamentioning
confidence: 99%
“…Examination of Table 2 shows that the number of strict endemics on Bali Ngemba is now nine, a drop of three from the 12 cited in Harvey et al (2004). This change has partly resulted from further survey work in other locations which has extended the known ranges of the species concerned so that they are no longer strict endemics (Cheek et al 2020b). It has also resulted from taxonomic revisions (Lachenaud 2019) and floristic studies (Couvreur et al 2021) that have reduced to synonymy three of the previously supposed strict endemics.…”
Section: The Endemic Plants Of Bali Ngembamentioning
confidence: 99%